PELEVELAN KEMAMPUAN LITERASI MATEMATIKA SISWA BERDASARKAN KEMAMPUAN MATEMATIKA DALAM MENYELESAIKAN SOAL PISA KONTEN CHANGE AND RELATIONSHIP - Kafifah, Anisa; Sugiarti, Titik; Oktavianingtyas, Ervin (Kadikma, 2018)
Based on the PISA results, the average Indonesian mathematical literacy score is 375. The average score is still below the average international math literacy score of 500. The purpose of this research is to describe students’ mathematics literacy ability based on mathematical ability in resolving the problem of PISA change and relationship content. Change and Relationship content is closely related to function and algebra. Determination of the level of student literacy skills seen from the fulfillment of level 1 indicators to level 6. The subject of this research were 33 students of X MIPA 7 grouped based on mathematical ability students with low, moderate and high. The results showed that maximal low-ability math students reached level 2. For students with moderate mathematical abilities the maximum was able to reach level 4 and maximal high-ability math students reached level 4. Keywords: PISA, Mathematical Ability, Mathematics Literacy.